Relationship between social identity and brand communication using spokes characters design features in Kellogg’s breakfast cereals - Noor Adzmee, Majidatul Farhana (2019)
Over the years, the spokes character has become an important aspects in the brand communication advertisement. This is due to the scholars thought on the importance of brand communication as the main function of brand communication was to enhance the brand loyalty and brand trust within several stakeholders such as; the customers, employees, suppliers, channel members, the media, government regulators, and the community. Even though the spokes characters’ design features have become an important aspect in creating spokes characters to represent the image of the company somehow, less studies had been done concerning the relationship between the social identity and the design features of spokes characters. Thus, the aim of this research was to determine on the relationship between the social identity and brand communication using the design features of spokes characters in Kellogg’s breakfast cereal across the six countries of the world which includes; South Africa, Japan, France, Mexico, United States of America and Australia. The social Identity was explained by the national culture using two cultural framework which were; Hofstede’s Cultural Framework and Hall’s Cultural Framework. A total of 81 Kellogg’s spokes characters were observed to identify the design features preferences based on the national culture indicators chosen from the literature. The independent observers also were appointed to compare the results using the Normality and Reliability Analysis to prevent the systematical error. The data were analyzed through the frequency analysis on features of spokes character according to the countries, mapping of national culture markers on the spokes character design features, and Statistical Analysis using the Cross-Tabulation Data and Chi Square. In conclusion, the finding of the study found that the design features of Kellogg’s spokes character across the six countries of the world has significant differences in most of the design indicators chosen. The findings also indicated that Social Identity influences the design features of spokes character across the six countries of the world. However, the research only focusing on one breakfast cereal brand hence, it is recommended for the future researcher to include several breakfast cereal brands to make more comparison between the spokes characters brands.